Cluster analysis for symptomatic management of Neisseria gonorrhoea and Chlamydia trachomatis in sexually transmitted infections related clinics in China - Ning, Ning; Weng, Rongxing; Zhang, Chunlai; Wen, Lizhang; Wang, Honglin; Ye, Jianbin; Li, Jing; Chen, Xiangsheng; Cai, Yumao (Frontiers in Public Health, 2022)
Objective: This study aimed to perform a cluster analysis of symptoms linked with NG and CT and to identify which cluster of symptoms were associated with higher risk of NG and CT. Study design: From April 15 to May 16, 2018, a cross-sectional study was conducted and patients attending STI-related clinics were recruited from 22 medical institutions in six districts of Shenzhen city. Methods: A structured questionnaire was used to collect social-demographic information as well as STI symptoms, and urine samples were collected for nucleic acid detection. Cluster analysis and logistic regression were used to examine the corresponding outcomes. Results: Among 8207 participants, the prevalence of CT and NG infection was 9.04% (742/8207) and 2.36% (194/8207), respectively. Among men outpatients, four clusters with distinct symptomatic patterns were identified. Unmarried, having casual sexual partners in the past six months, cluster 2 (OR = 6.70, 95%CI = 3.36-13.35), and cluster4 (OR = 24.53, 95%CI = 12.96-46.44) were risk factors associated with NG infection. Unmarried, cluster 2 (OR =2.54, 95%CI = 1.83-3.53), and cluster 4 (OR = 3.31, 95%CI = 2.37-4.61) were risk factors associated with CT infection. Among women outpatients, five clusters with distinct symptomatic patterns were identified. Aged 24 years old or below and cluster 3 (OR = 3.68, 95%CI = 1.61-8.39) were risk factors associated with NG infection. Aged 24 years old or below, being unmarried, having high school/secondary technical school education, and having junior high school or below education were risk factors associated with CT. Conclusions: Cluster of symptoms integrated into risk assessment for CT and NG infections suggested a new strategy of symptomatic management. Healthcare providers in STI clinics and resource-limited places may use this strategy to identify more potential patients and deliver adequate, acceptable, and equitable STI care for outpatients with high risk of STI Conclusions: Cluster of symptoms integrated into risk assessment for CT and NG infections suggested a new strategy of symptomatic management. Healthcare providers in STI clinics and resource-limited places may use this strategy to identify more potential patients and deliver adequate, acceptable, and equitable STI care for outpatients with high risk of STI